Striking a Balance: Navigating Tensions Between Collective and Member Goals in Boundary Organizations - Zobel, Ann-Kristin; Comello, Stephen (Organization Science, 2025)
Boundary organizations aim to facilitate collective efforts, but their collaborative arrangements often fall short of initial expectations, face member exits, or experience escalating conflicts. How do diverse members of these boundary organizations stay together and pursue collective goals despite tensions with their individual goals? Drawing on the concept of agency, we explore how members respond to these tensions and reshape the boundary organization’s goals to better align with their own, while maintaining collaboration for the pursuit of collective goals. Based on an in-depth longitudinal case study of a boundary organization in the energy sector, we developed a process model that explains how and why agency evolves over time. It outlines different trajectories through which members achieve a balance between collective and member goals, offering insights into how boundary organizations can either sustain themselves or fail. Our findings emphasize that goal pursuit is a dynamic process, where members continuously shift their focus between collective and member goals to maintain a balance over time. The process model explicates the agentic mechanisms behind these shifts in focus, revealing a dynamic interplay between two forms of agency that differ in their temporal orientation and locus of agency. We extend prior research that has focused on the governance structures and organizing practices in boundary organizations, by offering insights into why these boundary organizations may prevail, as they continuously shift their agency to navigate resurfacing tensions. Funding: This work was supported by the Swiss Competence Center for Energy Research–Competence Center for Research in Energy, Society and Transition (SCCER CREST) [Grant 1155000154]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.16973 .